Neuroplasticity - Insights of Neural Reorganization - Victor V. Chaban (IntechOpen, 2018)
This book provides comprehensive and up-to-date insights into emerging research trends on neuroplasticity with current or future treatments for neurodevelopment and neurodegenerative diseases. The authors discuss structural and functional changes associated with cortical remapping, sensory substitution, synaptic and non-synaptic compensatory plasticity due to brain damage, brain training, chronic pain, meditation, music, exercise and related states. Key features include pathogenesis, and existing and new therapies together with a pharmacological and non-pharmacological approach in clinical treatment and management. The authors are established experts that contributed significantly to a better understanding of the etiology of neuroplasticity. This book is recommended to healthcare providers, clinical scientists, students and patients.
English
Keywords: Life Sciences; Neuroplasticity; Neuroscience; Neurobiology